Mekanisme Bagi Hasil dalam Kebijakan Moneter Syariah : Prinsip, Praktik, dan Implikasinya Terhadap Stabilitas Ekonomi - Fathin Nur Muhammad; Firman Hidayatullah; Muhammad Saddam Al-andalusi; Rasidah Novita Sari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The principle of profit sharing based on the concept of risk-sharing offers an alternative approach that is in line with sharia values, in contrast to the conventional interest system. This mechanism is implemented through instruments such as mudharabah and musharakah that support the financing of productive projects. However, its implementation faces challenges related to income fluctuations that can affect the stability of Islamic financial institutions. This research highlights the importance of innovation to increase the effectiveness of sharia monetary policy for inclusive and sustainable economic growth.